Myasthenia Gravis and Related Disorders (Current Clinical Neurology,, 2018)
The third edition of this important, gold-standard title outlines a range of significant advances in the study and understanding of myasthenia gravis. The overarching goal of this new edition is identical to the first and second -- to provide the clinician and the scientist with a common resource for understanding the profound achievements in the clinical, translational, and basic sciences of neuromuscular transmission disorders. In addition to several new authors and an extensive update of all chapters, this third edition includes summaries of pre-clinical research standards for autoimmune MG, along with a broad summary of MG clinical trial performance. The now greater understanding of the clinical presentation of MuSK-related MG and identification of potential new autoantigens, including LRP-4, is discussed. The development of treatment guidelines by groups in Japan, the United Kingdom, Germany, and an international consortium is also outlined. Myasthenia Gravis and Related Disorders, Third Edition, is an invaluable resource for meeting the many and varied needs of clinicians who treat patients with myasthenia gravis.